The role of metabolic score for visceral fat in the prediction of atrial fibrillation recurrence risk after catheter ablation - Ma, Yazhe; Gao, Xiaolong; Sun, Jianying; Kuang, Xiaohui; Zhang, Xi; Wei, Feiyu; Ma, Tao; Cui, Yanju; Guo, Jia; Wu, Peng; Liu, Jiangwen; Fan, Jie (Frontiers in Endocrinology, 2025)
BackgroundPrevious studies show that visceral fat tissue (VAT) play an important role in atrial fibrillation (AF). The metabolic score of visceral fat (METS-VF), a new surrogate to estimate VAT, is associated with cardiovascular mortality risk. In this study, we try to investigate the association between METS-VF and the risk of AF recurrence after catheter ablation.Methods478 consecutive patients underwent catheter ablation were obtained and used to assess the relationship between METS-VF and the risk of AF recurrence. Cox regression was used to calculate the hazard ration (HR) of METS-VF for the risk of AF recurrence. Restricted cubic splines (RCS) was used to assessed the linear relationship between METS-VF and the AF recurrence risk.ResultsA total of 112(23.4%) patients experienced AF recurrence during 18.0 ± 9.6 months follow-up. The AF recurrence rate was significantly higher in the highest quartile of METS-VF than the other three quartiles (log rank = 0.021). In the univariate cox regression, LAD, and MET-VF were associated with AF recurrence (p<0.0001). In the multiple Cox regression results, compared with the participants with lowest METS-VF (Q1), the hazard ratio (HR) (95% CI) for the AF recurrence risk was 1.29 (0.73, 2.29) for Q2 (p=0.39), 1.59 (0.88 – 2.87) for Q3 (p=0.12), and 2.22 (1.20, 4.12) for Q4 (p<0.01) respectively.ConclusionsMETS-VF was positively associated with the elevated AF recurrence risk. Our findings show that the METS-VF could be used to AF recurrence risk stratification.